COMPARATIVE PHRASEOLOGY: CROSS-LINGUISTIC EQUIVALENCE AND PROBLEMS IN TRANSLATING IDIOMS - Khikmatova Dilrabo Pulatovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article interprets the characteristics of somatic phraseological units in the Russian and Uzbek languages, their semantic specificity, and the problems of adequately conveying them in bilingual dictionaries.This article examines how Russian-Uzbek translation dictionaries reflect phraseological units and the extent to which their imagery and cultural flavor are preserved. Particular attention is paid to translation difficulties associated with interlingual asymmetry and national-cultural differences.